Nickel-catalyzed hydroalkylation of 1, 3-dienes with malonates using a homoallyl carbonate as the 1, 3-diene and hydride source. (30th March 2021) - Tsuji, Hiroaki; Takahashi, Yoshiyuki; Kawatsura, Motoi
Graphical abstract: Highlights: Nickel-catalyzed hydroalkylation of 1, 3-dienes. A homoallyl carbonate as a surrogate for the 1, 3-diene and hydride source. Malonates were used as a carbon pronucleophile. Abstract: The use of a malonate nucleophile in the transition metal-catalyzed hydroalkylation of 1, 3-dienes remains immature. Herein, we report the nickel-catalyzed hydroalkylation of 1, 3-dienes with malonates using a homoallyl carbonate as the 1, 3-diene and hydride source. A broad range of homoally carbonates and malonate derivatives were well tolerated under a Ni/DPEphos catalyst system, providing the corresponding 1, 2-hydroalkylation products in 40–94% yields with excellent regioselectivity (32 examples). We also suggested the possible reaction mechanism for the nickel-catalyzed hydroalkylation of in situ generated 1, 3-dienes with malonates.